SUSTAINABLE FUTURE: ENVIRONMENTAL POLICY FOR A GREENER EARTH - Edy Sony; Runik Machfiroh; I Wayan Gede Suacana; Iyad Abdallah Al- Shreifeen (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Environmental policy will realize environmental protection and management that always considers every activity if we want to utilize natural resources and the environment to meet our needs. For this reason, the aim of environmental protection and management is fundamentally in the area of legal methods, so that policy officials responsible for the environment can interpret, understand and implement the law. The effectiveness of environmental protection policies also includes the development of legal instruments that support the application of the principles of sustainability, integration and shared responsibility in managing natural resources. We are all responsible for providing a better future for future generations. A greener, healthier and fairer future. With a healthy environment, we can give them the opportunity to experience a quality life, like the one we feel today. We must ensure that we do not steal their future, but leave a valuable legacy of a healthy and sustainable environment. This article employs a form of literature review that includes hypotheses pertaining to the issue under investigation. This study examines the implications environmental policies have on the environment, effective methods for formulating and implementing environmental policies, the effectiveness and impact of current environmental policies, and recommended environmental policies for a greener future.